Chlamydomonas reinhardtii mutants deficient for Old Yellow Enzyme 3 exhibit increased photooxidative stress. (15th January 2023) - Böhmer, Stefanie; Marx, Christina; Goss, Reimund; Gilbert, Matthias; Sasso, Severin; Happe, Thomas; Hemschemeier, Anja
Abstract: Old Yellow Enzymes (OYEs) are flavin‐containing ene‐reductases that have been intensely studied with regard to their biotechnological potential for sustainable chemical syntheses. OYE‐encoding genes are found throughout the domains of life, but their physiological role is mostly unknown, one reason for this being the promiscuity of most ene‐reductases studied to date. The unicellular green alga Chlamydomonas reinhardtii possesses four genes coding for OYEs, three of which we have analyzed biochemically before. Ene‐reductase CrOYE3 stood out in that it showed an unusually narrow substrate scope and converted N ‐methylmaleimide (NMI) with high rates. This was recapitulated in a C. reinhardtii croye3 mutant that, in contrast to the wild type, hardly degraded externally added NMI. Here we show that CrOYE3‐mediated NMI conversion depends on electrons generated photosynthetically by photosystem II (PSII) and that the croye3 mutant exhibits slightly decreased photochemical quenching in high light. Non‐photochemical quenching is strongly impaired in this mutant, and it shows enhanced oxidative stress. The phenotypes of the mutant suggest that C. reinhardtii CrOYE3 is involved in the protection against photooxidative stress, possibly by converting reactive carbonyl species derived from lipid peroxides or maleimides from tetrapyrrole degradation.